2022
DOI: 10.1017/pds.2022.124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Affordance-Based Requirements Generation Tool for Speech And Language Therapeutic Toys

Abstract: Task clarification poses various challenges to designers as they need to understand the different needs of users before translating the requirements into specifications and aptly conceiving product concepts in the subsequent design stage. This paper presents a descriptive study for the evaluation of a framework and its implementation as a computer-based prototype tool, proposed to assist designers in generating and understanding affordance-based requirements for speech and language therapeutic toys. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a previous study by Balzan (2022) a set of twelve elements were identified which provide designers with explicit knowledge regarding the considerations which should be done when eliciting requirements for a conventional SALTT. Balzan et al (2022) argue that each element is vital for the design of a SALTT and an absence of any of the components will negatively impact the effectiveness and usefulness (referred to as the potential) of an artefact being designed for use in DLD therapy.…”
Section: The Speech and Language Therapy Potential Modelmentioning
confidence: 99%
“…In a previous study by Balzan (2022) a set of twelve elements were identified which provide designers with explicit knowledge regarding the considerations which should be done when eliciting requirements for a conventional SALTT. Balzan et al (2022) argue that each element is vital for the design of a SALTT and an absence of any of the components will negatively impact the effectiveness and usefulness (referred to as the potential) of an artefact being designed for use in DLD therapy.…”
Section: The Speech and Language Therapy Potential Modelmentioning
confidence: 99%